1982
DOI: 10.1002/jcp.1041120208
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin E in cellular energy metabolism in cultured adrenocortical cells

Abstract: ACT cells, a bovine adrenocortical cell clone, are rapidly arrested and killed by 2 mM aminooxyacetate, an inhibitor of transamination reactions. Toxicity of aminooxyacetate to cultured bovine adrenocortical cells was previously linked to a high ratio of capacity for oxidation of glutamine relative to pyruvate and was reversible by adding excess glutamine. The toxic effects of aminooxyacetate were shown in the present study to be completely prevented by the simultaneous addition of low concentrations ( < 100 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Thus, an early indication of disturbed mitochondrial function in cells in culture is a shift from oxidative use of pyruvate to use of glutamine (Breen & Shreffler, 1979;Reitzer et al, 1979;Hornsby & Gill, 1981). This transition occurs more rapidly in atmospheric oxygen than in 2% oxygen and is slowed by efficient removal of oxidative species (Hornsby & Gill, 1981;Hornsby, 1982), thereby implicating oxidative damage in the causation of the metabolic transition. Hornsby (1982) suggested that the ubiquinone cycle of mitochondria in cells in culture is interrupted by lipid radicals formed by lipid peroxidation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, an early indication of disturbed mitochondrial function in cells in culture is a shift from oxidative use of pyruvate to use of glutamine (Breen & Shreffler, 1979;Reitzer et al, 1979;Hornsby & Gill, 1981). This transition occurs more rapidly in atmospheric oxygen than in 2% oxygen and is slowed by efficient removal of oxidative species (Hornsby & Gill, 1981;Hornsby, 1982), thereby implicating oxidative damage in the causation of the metabolic transition. Hornsby (1982) suggested that the ubiquinone cycle of mitochondria in cells in culture is interrupted by lipid radicals formed by lipid peroxidation.…”
Section: Discussionmentioning
confidence: 95%
“…The ubiquinone cycle, with ubiquinone (Q), ubisemiquinone (QH*), and ubiquinol (QH2) is shown to be interrupted by lipid radical formation (L*). SDH: succinate dehydrogenase; NADH-dh: NADH dehydrogenase (after Hornsby, 1982). Embryos were cultured in aminooxyacetate from 28 to 70 h after injection of mice with human chorionic gonadotrophin and they were then transferred to T6 + bovine serum albumin.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation may be a difference in the relative activity of the two halves of the Krebs cycle. The ratio of glutamine to pyruvate metabolism has been shown to increase with proliferation of bovine adrenocortical cells in culture (Hornsby and Gill 1981), possibly because the NAD+substrate-dehydrogenases in the oxaloacetate to 2-oxoglutarate segment of the Krebs cycle are more sensitive to inhibition by NADH than are those in the segment from 2-oxoglutarate to oxaloacetate (Hornsby 1982). Similar mechanisms during expansion and hatching of the cattle blastocyst, may be responsible for the apparent increased significance of the activity of the 2-oxoglutarate-to-oxaloacetate segment of the Krebs cycle, relative to the activity of the pathway from pyruvate to 2-oxoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…The production of 14c02 from [2-14c] pyruvate was used as a measure of the activity of the entire Krebs cycle, and the production of 3~2~ from L-[3,4-3~(~)]glutamine (via deamination to glutamate and 2-oxoglutarate) was used as a measure of the activity of the 2-oxoglutarate-to-oxaloacetate segment (Hornsby and Gill 1981;Hornsby 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Growth of most mammalian cells in vitro requires high levels of glutamine (21,22), although this requirement may be an artifact of the tissue-culture system (23). High rates of glutamine use may be characteristic oftumor cells both in vitro and in vivo (24)(25)(26), and experimental cancer therapies have been developed based on depriving tumor cells of glutamine (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%